Pelaksanaan Pembelajaran Blended Learning Di Masa Pandemi Covid-19 Pada Kelas Iv Sd Negeri 1 Duren - Titis Suci Widyowati; Wawan Priyanto; Sukamto Sukamto (Jurnal Sultra Elementary School, 2022)
The Covid-19 pandemic has transformed the learning process at SD Negeri 1 Duren, which traditionally relied on face-to-face instruction, into a blended learning system that combines offline (luring) and online (daring) learning. The purpose of this study is to examine the implementation process of blended learning in Grade IV of SD Negeri 1 Duren and to identify its strengths and weaknesses. This research uses a qualitative method, with data collected through observation, interviews, and documentation. The research subjects include fourth-grade students and their teacher. The findings indicate that online and offline learning were conducted simultaneously. The WhatsApp application was used as the main online learning platform, while offline learning took place at school based on the materials shared through the WhatsApp group. The implementation of blended learning presents several challenges, such as students’ limited understanding of the material and poor time management. However, it also offers advantages, including the ease for teachers to distribute learning materials to all students.